Effects of Virtual Learning to Learning Process in Private University College in Malaysia - Ong, Le Vin (2009)
Virtual learning has been the new learning process that overcomes the boundaries of geographical barrier in between the lecturer and students. Even though virtual learning breaks the barriers between lecturer and students, however there are still some problems that occur in the process of it. Empirical study shows the limitations of virtual learning, which affects the design of virtual learning. Therefore, the main goal of this research is to present answers and suggestions to the research questions. This research is a casual research where quantitative research been used. The results of the studies were then analyzed and scrutinized based on the findings. The conclusion of the research entails the answers for the research questions. Education through virtual environment is an enhancement of traditional physical education. Students are encouraged to be participating and independent in learning which could close the communication gap between lectures and students.